Ergonomic Postural Risk Monitoring of Worker Working on Lathe Machine - Kakde, A.M; Kherde, S.M (International Journal of Engineering and Management Research, 2026)
The operation of lathe machines in manufacturing industries often exposes workers to awkward postures, repetitive motions, and prolonged static positions that may contribute to musculoskeletal disorders (MSDs) and reduced productivity. Ergonomic assessment and monitoring of postural risks are therefore essential to ensure worker safety, efficiency, and overall well-being. This study focuses on the ergonomic postural risk monitoring of workers operating lathe machines using observational methods and posture evaluation tools such as RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire Body Assessment). The analysis highlights high-risk postures associated with bending, twisting, and extended arm reach during machining, loading, and unloading tasks. Data collected were further examined to identify critical risk zones and propose corrective ergonomic interventions such as workstation redesign, tool placement optimization, and work-rest scheduling. The findings indicate that ergonomic interventions not only minimize postural risks but also enhance operator comfort, reduce fatigue, and improve productivity. This study emphasizes the importance of integrating ergonomic monitoring systems into machine shop environments for sustainable industrial practices.